The Effect of Working Time on Productivity and Firm Performance: A Case of Nepalese commercial banks - Mahato, Lal Babu (Nepalese Journal of Management, 2025)
This study examines the effect of working time on productivity and firm performance in Nepalese commercial bank. Firm performance and productivity are the dependent variable. The selected independent variables are working hours, work schedule flexibility, break time policies, overtime practices and employee engagement initiatives. The primary source of data is used to assess the opinions of respondents regarding working hours, work schedule flexibility, break time policies, overtime practices, employee engagement initiatives and firm performance and productivity. The study is based on primary data of 136 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of working time on productivity and firm performance in Nepalese commercial banks. The study showed a positive impact of working hours on productivity and firm performance. It indicates that working hours service leads to increase in productivity and firm performance. Similarly, the study showed a positive impact of work schedule flexibility on productivity and firm performance. It indicates that easily available of work schedule flexibility leads to an increase in productivity and firm performance. Likewise, the study also revealed a positive impact of break time policies on firm performance and productivity. It indicates that break time policies lead to an increase in productivity and firm performance. Further, the study observed a positive impact of overtime practices on productivity and firm performance. It indicates that higher the overtime practices, higher would be the productivity and firm performance. In addition, the study observed a positive impact of employee engagement initiatives on productivity and firm performance. It indicates that employee engagement initiatives lead to an increase in productivity and firm performance.